KAJIAN LITERATUR OUTDOOR LEARNING BERBASIS INKUIRI DALAM MENINGKATKAN KETERAMPILAN PROSES SAINS DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Sunefti, Aida; Sukma, Elfia; Kharisma, Inggria (STKIP Subang, 2026)
The purpose of this study was to investigate how inquiry-based outdoor learning can enhance primary school students' science process abilities and learning outcomes. The limited development of students' scientific skills and subpar learning outcomes, which are frequently linked to teacher-centered instructional approaches and the underutilization of the surrounding environment as a contextual learning resource, provide the backdrop for this study. This study used a literature review strategy and a qualitative methodology. Selected scientific journal articles, books, and pertinent earlier research on inquiry-based learning and outdoor learning were the sources of the data. While data analysis employed descriptive qualitative methodologies by organizing, comparing, and synthesizing findings from multiple sources, data collecting was accomplished through a systematic assessment of the literature.Based on the reviewed literature, the results show that inquiry-based outdoor learning helps students build their science process abilities, especially when it comes to observing, classifying, questioning, and conveying discoveries. Additionally, this method is linked to superior learning outcomes, as demonstrated by students' increased academic success and conceptual comprehension. Additionally, outdoor learning activities offer contextualized and meaningful learning opportunities that boost student participation and engagement. Inquiry-based outdoor learning is therefore seen as a pertinent strategy to promote efficient, contextual, and student-centered scientific instruction in primary school.